WORKSHOP PEMBUATAN LEARNING MANAJEMEN SYSTEM (LMS) BERBASIS GOOGLE SITES BAGI GURU SMK - Tuah, Yayan Adrianova Eka; Anyan, Anyan; Rifai, Muhamad; Elti P, Kristiani; Pangestu, Robby (Jurnal Pengabdian Masyarakat Khatulistiwa, 2022)
ABSTRACTIn this era of industrial revolution, the teaching and learning process is transformed into competency-based industrial learning with a focus on automation using information technology. Each platform provided certainly has advantages and disadvantages in utilizing learning resources for students, considering that geographically, especially in Sintang District, West Kalimantan, internet access is not evenly distributed. With this uneven internet access, the Google Sites platform can be an alternative in its utilization, while this platform is lightweight, easy to understand, responsive, and free, as well as easily accessible by students. Some learning difficulties can be experienced by students in learning. Google Sites can be used by teachers to upload videos and learning materials as well as topic characteristics. Through the Google Sites platform, teachers can integrate several other platforms so that Google Sites can be used as a Learning Management System (LMS). The data analysis conducted is qualitative and quantitative descriptive. The results of the dedication activity show that overall the implementation of the activity has run well and obtained a positive or satisfactory response from participants (indicated by an average score of 3.08 based on questionnaires distributed to respondents). The implementation of the activity was carried out in three stages of activities as follows: providing teaching materials and designing Google Sites LMS, compiling LMS assets, and practical activities in compiling Google Sites LMS. Overall, the series of activities were considered positive by participants.Keywords: industrial revolution, competency-based learning, Google Sites, Learning Management System (LMS), internet accessABSTRAKMasa era revolusi industri sekarang ini, proses belajar dan mengajar bertransformasi pada pembelajaran berbasis kompetensi industri dengan konsep berpusat pada otomatisasi dengan bantuan teknologi informasi. Setiap platform yang disediakan tentunya memiliki kelebihan dan kekurangan dalam pemanfaatan sumber belajar peserta didik, mengingat secara geografis khususnya Kabupaten Sintang Kalimantan Barat, akses internet tidak semua merata. Dengan akses internet yang tidak merata ini, platform google sites dapat menjadi alternatif dalam pemanfaatannya, sembari platform ini ringan, mudah dipahami, responsif dan gratis serta mudah diakses oleh peserta didik. Beberapa kesulitan belajar dapat dialami oleh peserta didik dalam belajar. Google sites dapat dimanfaatkan oleh guru untuk mengunggah video dan materi pembelajaran serta karakteristik topik. Melalui platform google sites guru dapat mengintegrasikan beberapa platform lainnya sehingga google sites dapat dijadikan sebagai Learning Management System (LMS).. Analisis data yang dilakukan adalah deskriptif kualitatif dan kuantitatif. Hasil kegiatan pengabdian menunjukan bahwa secara keseluruhan pelaksanaan kegiatan telah berjalan dengan baik dan mendapatkan respon positif atau memuaskan peserta (ditunjukan dengan nilai rata-rata sebesar 3.08 berdasarkan angket responden yang disebarkan), Pelaksanaan kegiatan dilakukan dengan tiga tahapan kegiatan sebagai berikut: memberikan materi bahan ajar dan desain LMS Google Sites, menyusun asset-aset LMS, dan kegiatan praktik menyusun LMS Google Sites. Secara keseluruhan dari rangkaian kegiatan tersebut dipandang positif oleh peserta.Kata Kunci: revolusi industri, pembelajaran berbasis kompetensi, Google Sites, Sistem Manajemen Pembelajaran (LMS), akses internet